(untitled) (Książnica Śląska, 2025)
The subject of this article is participation of members of Association of Silesian Song Ensembles in Silesian Uprisings. Małgorzata Witowska refers to a manuscript from the resources of the Silesian Library titled Materials for History of Silesian Choirs and Song Ensembles. The author not only describes beginning of of the Silesian singing movement and their difficult situation resulting from German repressions, but also gives examples of their contribution to insurgent actions and propaganda activities before the Plebiscite.